ANALISIS PENDAPATAN RUMAH TANGGA PETANI KELAPA SAWIT POLA SWADAYA DI DESA SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Sari, Dian Novita; Yulida, Roza; Yusri, Jum’atri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this study was to determine the household income pattern of non-oil palm farmer in Senama Nenek Village Tapung District Kampar Regency, to analyze the structure of household income pattern of non-oil palm farmers in Senama Nenek Village Tapung District Kampar Regency and to determine the condition of the coconut farmer household welfare palm patterns of self-help Senama Nenek Village Tapung District Kampar Regency. This research was conducted in Senama Nenek Village Tapung District Kampar Regency is a district with the largest oil production people in Kampar Regency. This research was conducted by survey method, ie through interviews with palm oil farmers self-patterns. Samples were taken by simple random sampling technique with a number of sample as many as 30 people. Data analysis consisted of analysis of profits / income, income structure analysis, and well-being. The study found that the net income of non-oil palm farmers in Senama Nenek Village Rp 35.815.012 / Land / Year. As for family work income received by farmers was Rp 36.028.345 / Land / Year. Implicit costs consist of depreciation costs Rp 139.329 / year and TKDK Rp 213 333 / year. While the explicit costs consist of costs fertilizer Rp 5.003.870 / year, the cost of pesticides Rp1.008.867 / year and costs TKLK 4.255.367 / year. The structure of non-palm farmers' income consists of income is from agriculture and non-agricultural income. The average number of net income from agriculture earned by oil palm farmers self-patterns of Rp 36.028.345,-. As for non-agricultural income, the average earned by oil palm growers governmental pattern of Rp 2.800.000,-. So that the total income received by farmers is Rp 38.028.345,-. Based on the criteria of basic needs and is measured by indicators of well-being obtained that all smallholders as many as 30 people belonging to prosperous farmers. Based on the results obtained that the farmers are quite prosperous. Keywords: Palm, Farmers Organization, Revenues, Expenses, Welfare